Percutaneous mitral valve repair with the MitraClip NT™ system in a patient presenting with prolonged cardiogenic shock. Issue 11 (23rd September 2017) - Buckert, Dominik; Markovic, Sinisa; Kunze, Markus; Wöhrle, Jochen; Rottbauer, Wolfgang; Walcher, Daniel
Key Clinical Message: The MitraClip NT™ system for the treatment of severe mitral valve regurgitation is effective and safe – even for patients suffering from cardiogenic shock. The use of an intra‐aortic balloon pump expands the range of possible applications to this particular group of challenging patients. Abstract : The MitraClip NT™ system for the treatment of severe mitral valve regurgitation is effective and safe – even for patients suffering from cardiogenic shock. The use of an intra‐aortic balloon pump expands the range of possible applications to this particular group of challenging patients.